2021
DOI: 10.1177/08971900211010678
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GLP-1 Receptor Agonists in Combination With Multiple Daily Insulin Injections for Type 2 Diabetes

Abstract: Objective: To assess the available literature evaluating the efficacy and safety of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) with multiple daily insulin injections (MDII). Data Sources: A literature search of MEDLINE and Embase was performed (2004 to May 2020) using the following search terms: glucagon-like 1 receptor agonist, liraglutide, albiglutide, dulaglutide, exenatide, semaglutide, diabetes mellitus, and prandial insulin or bolus insulin. Additional references were obtained from cross-refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Similar findings were made in the study by Sassenrath et al, which showed that the combination of insulin and a GLP-1RA improves blood glucose control and reduces the dose of insulin required, without increasing the incidence of hypoglycemia. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were made in the study by Sassenrath et al, which showed that the combination of insulin and a GLP-1RA improves blood glucose control and reduces the dose of insulin required, without increasing the incidence of hypoglycemia. 46 …”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In addition, basal insulin and GLP-1RA have a synergistic effect that can further improve blood glucose control and reduce the adverse side effects of each ingredient, such as weight gain, hypoglycemia and gastrointestinal symptoms. [29][30][31] Therefore, the combination of weekly insulin and weekly GLP-1RA is a promising strategy. Future studies could explore the feasibility of this combination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that the addition of GLP-1 RA to multiple daily insulin injections reduced A1c and total daily insulin doses without increasing hypoglycemia frequency or other adverse events. 14 Clinicians may be more prone to pre-emptively reducing insulin doses when starting therapy with semaglutide to mitigate hypoglycemia risk or simplify complex medication regimens, as current literature suggests that semaglutide is a more potent GLP-1 RA compared to liraglutide. 8,9 Importantly, the baseline insulin dose per day was higher in the semaglutide group vs. the liraglutide group which may explain the finding of larger reductions in insulin doses seen in the semaglutide group.…”
Section: Discussionmentioning
confidence: 99%